Decolonizing drug policy - Colleen Daniels; Aggrey Aluso; Naomi Burke-Shyne; Kojo Koram; Suchitra Rajagopalan; Imani Robinson; Shaun Shelly; Sam Shirley-Beavan; Tripti Tandon (Harm Reduction Journal, 2021)
Abstract This paper reviews evidence of how drug control has been used to uphold colonial power structures in select countries. It demonstrates the racist and xenophobic impact of drug control policy and proposes a path to move beyond oppressive systems and structures. The ‘colonization of drug control’ refers to the use of drug control by states in Europe and America to advance and sustain the systematic exploitation of people, land and resources and the racialized hierarchies, which were established under colonial control and continue to dominate today. Globally, Black, Brown and Indigenous peoples are disproportionately targeted for drug law enforcement and face discrimination across the criminal system. These communities face higher arrest, prosecution and incarceration rates for drug offenses than other communities, such as majority populations, despite similar rates of drug use and selling among (and between) different races. Current drug policies have contributed to an increase in drug-related deaths, overdoses and sustained transnational criminal enterprises at the expense of the lives of people who use drugs, their families and greater society. This review provides further evidence of the need to reform the current system. It outlines a three-pillared approach to rebuilding drug policy in a way that supports health, dignity and human rights, consisting of: (1) the decriminalization of drugs and their use; (2) an end to the mass incarceration of people who use drugs; (3) the redirection of funding away from ineffective and punitive drug control and toward health and social programs.